2013
DOI: 10.3389/fnsys.2013.00029
|View full text |Cite
|
Sign up to set email alerts
|

Learning not to feel: reshaping the resolution of tactile perception

Abstract: We asked whether biased feedback during training could cause human subjects to lose perceptual acuity in a vibrotactile frequency discrimination task. Prior to training, we determined each subject's vibration frequency discrimination capacity on one fingertip, the Just Noticeable Difference (JND). Subjects then received 850 trials in which they performed a same/different judgment on two vibrations presented to that fingertip. They gained points whenever their judgment matched the computer-generated feedback on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 58 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…Finally, the assumptions used here, of a 7% JND, were based on existing work. However, studies have also found that providing feedback, training, and frequency changes can have an impact on JND 30 . Additionally, visual feedback has also been shown to impact user JND 50 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the assumptions used here, of a 7% JND, were based on existing work. However, studies have also found that providing feedback, training, and frequency changes can have an impact on JND 30 . Additionally, visual feedback has also been shown to impact user JND 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Hands and fingers are extremely sensitive to the sense of touch, and it has been found that intentional training can improve surgeon skills 24 26 . A JND of [5, 10]% change has been observed during [2, 10] N loads between fingers or in elbow extension, but can vary based on finger, training, and frequency 27 30 . Work on haptic devices has found higher JNDs, including 23 ± 13% and 34 ± 24% detectable changes for force and torque on the ranges of [0.4,8.8] N and [20,410] N mm, respectively 31 .…”
Section: Introductionmentioning
confidence: 99%